The importance of brain mapping for rehabilitation in birth nonprogressive neuromuscular diseases - Tolmacheva, Aleksandra; Agranovich, Olga; Blagovechtchenski, Evgeny (Frontiers in Neuroimaging, 2024)
While motor mapping has been extensively studied in acquired motor conditions, a lack has been observed in terms of research on neurological disorders present since birth, with damage to the spinal cord and peripheral nerves (hence, defined in this study as nonprogressive neuromuscular diseases). Despite an injury at the level below the brain, the subsequent changes in the motor system involve cortical reorganization. In the scientific community, the need for a comprehensive approach targeting the brain is increasingly recognized for greater motor recovery in these patients. Transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) are the most utilized techniques for motor mapping. The knowledge obtained through motor mapping may be used to develop effective individual neuromodulation therapy that helps in functional motor recovery. This brief review compares the results of the brain mapping of a few existing studies in individuals with nonprogressive motor disorders of nonbrain origin present at birth to the brain mapping of individuals with similar acquired motor conditions. The review reveals some particular features in terms of central adaptation in individuals with birth conditions compared to their acquired counterparts, such as the nonsomatotopic presentation of involved muscles in the sensorimotor cortex and nonadjacent cortical areas. This topic is undoubtedly intriguing, justifying further research in the field. This review also discusses the benefits these patients can obtain from neuromodulation therapy addressed to the central nervous system and the importance of individual neurophysiological assessment in designing rehabilitation therapy for children with birth motor disorders.